The Western “Alliance” and the Middle East in the Early 1970s - Sakkas, John (Études helléniques / Hellenic Studies, 2006)
The watershed for the European Community’s involvement in the Middle East came during the aftermath of the ‘October War’ and the Brussels and Copenhagen declarations of 1973, which marked the beginning of what was subsequently called the Euro-Arab Dialogue. This article examines the development of the Community’s collective approach to the Arab world in the early 1970s as well as the negative response of the Americans, who did not encourage any independent European role in the Middle East. The European reaction to this challenge from Washington was characteristic of the lack of sufficient unity both internally and externally.